2022
DOI: 10.1038/s41379-022-01070-2
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic germinal centers in the thymus accurately predict prognosis of myasthenia gravis after thymectomy

Abstract: The ability of thymic histopathology to predict the long-term impact of thymectomy in non-thymomatous myasthenia gravis (NTMG) is mainly uncharted. We applied digital pathology to quantitatively characterize differences of thymic histology between early-onset (EOMG) and late-onset MG (LOMG) and to investigate the role of thymic changes for thymectomy outcomes in MG. We analyzed 83 thymic H&E slides from thymectomized NTMG patients, of which 69 had EOMG and 14 LOMG, using digital pathology open-access softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Another recent key paper from a Finnish biobank highlighted the pathological relevance of thymic GC in EOMG. In this most thorough digital pathological analysis of thymi from patients with myasthenia gravis to date, the authors found a clear correlation between the numbers of GC and AChR-ab seropositivity in EOMG but, interestingly, not in late-onset MG (LOMG) [20 ▪▪ ]. A similar correlation between the number GC and AChR-ab-titers had previously been reported from the histological analysis of 1035 thymi of a French database [21].…”
Section: What Do We Know About the Underlying Pathophysiological Mech...supporting
confidence: 77%
See 1 more Smart Citation
“…Another recent key paper from a Finnish biobank highlighted the pathological relevance of thymic GC in EOMG. In this most thorough digital pathological analysis of thymi from patients with myasthenia gravis to date, the authors found a clear correlation between the numbers of GC and AChR-ab seropositivity in EOMG but, interestingly, not in late-onset MG (LOMG) [20 ▪▪ ]. A similar correlation between the number GC and AChR-ab-titers had previously been reported from the histological analysis of 1035 thymi of a French database [21].…”
Section: What Do We Know About the Underlying Pathophysiological Mech...supporting
confidence: 77%
“…Supporting this notion, the numbers of germinal centers (GC) in the Finish study correlated well with a better postoperative outcome after thymectomy in EOMG. Further evidence for the role of thymic B-cell maturation as a driver of the disease has been provided by a recent report showing an increase of plasmablasts within the thymus of patients with nonthymomatous myasthenia gravis in comparison to controls and a correlation of their numbers with the preoperative disease activity [22 ▪▪ ] An assessment of GC in thorough histological analyses of postoperative thymi could thus have a potential in the outcome prediction after thymectomy [20 ▪▪ ].…”
Section: What Do We Know About the Underlying Pathophysiological Mech...mentioning
confidence: 99%
“…It is known that T cell dependent ASC production can occur through both EF and GC routes ( 2 , 52 ). While ectopic GCs have been observed in the autoimmune THY ( 27 29 , 53 ), this does not appear to be a major route of THY ASC production under healthy conditions. This conclusion is supported by experiments that used Icosl -/- and CD4-Cre Bcl6 fl/fl mice which lacked functional T follicular helper (T FH ) cell signals yet still produced normal amounts of THY ASCs ( 35 ).…”
Section: Current Knowledge In the Fieldmentioning
confidence: 87%
“…Several autoimmune diseases possess alterations in the THY that include B cell activation, GC formation and/or increased production of ASCs ( 27 29 , 43 , 53 ). Importantly, this leads to functional consequences including destruction of the THY microenvironment as well as production of auto-Abs which promote cellular pathology and loss of organ function ( 26 , 29 , 43 , 53 ). This is perhaps not surprising given that the THY is inherently enriched for B cells with autoreactivity ( 46 , 48 ).…”
Section: Looking Towards the Future: Insights Into Autoimmunity?mentioning
confidence: 99%
“…Because most patients in our study had thymoma-related OMG, 50 years may not be suitable as a cut-off age in our study cohort, or in an OMG with thymoma cohort. Moreover, Sarkkinen et al [ 25 ] recently reported that ectopic germinal centres, which can predict better post-thymectomy outcomes in NTMG, are more prevalent in early onset NTMG thymus. In consideration of the potential differences in thymic histopathology in NTMG patients of different ages, we further analysed the proportion of early-onset and late-onset cases in our NTOMG sample set.…”
Section: Discussionmentioning
confidence: 99%